Reconstituting the state in Africa - Agbese, Pita Ogaba; Kieh, George Klay (Palgrave Macmillan, 2007)
Contributors to this volume highlight the failure and socio-economic and political problems of post-colonial African state and make constructive and convincing suggestions of how the problems can be addressed. They do not argue for the scrapping of the state but its reconstitution in ways that will enable it to be people's-oriented.